ADSORPSI ION LOGAM Pb2+ DENGAN ARANG AKTIF MAHKOTA NANAS (Ananas comosus (L.) Merr) TERMODIFIKASI KITOSAN - Arsyakia, Tarisa; Koesnarpadi, Soerja; Lianasari, Ika Yekti (JURNAL ATOMIK, 2025)
Pineapple (Ananas comosus (L.) Merr) is one of the most widely produced plants in Indonesia. Pineapple crown can be classified as solid waste that has an impact on the environment. Another problem of environmental pollution is heavy metals such as lead. In this study, modification was carried out by adding chitosan to the activated charcoal prepared from pineapple crown powder waste. The purpose of this study was to determine the characterization of chitosan-modified pineapple crown activated charcoal using Fourier Transform Infrared (FTIR) and Scanning Electron Microscopy (SEM), determine the optimum adsorption conditions based on variations in pH, contact time and concentration of Pb2+ metal and determine the percent absorption and adsorption capacity. The results of FT-IR characterization of pineapple crown charcoal, chitosan and chitosan-modified activated charcoal indicated the presence of O-H (streching), N-H, C-H (streching), C=C aromatic and C-H (bending) groups, and in pineapple crown charcoal and chitosan-modified pineapple crown activated charcoal also indicated C-O-C groups while chitosan indicated C-N groups. In the results of SEM characterization, pineapple crown charcoal has a smooth, chitosan has a rough and chitosan-modified activated charcoal has a slightly rough surface and is still tightly bound to each other. The optimum conditions for adsorption of chitosan-modified activated charcoal on Pb2+ metal ions at pH 4 with a contact time of 60 minutes and a concentration of 75 mg/L. The results of the adsorption capacity test at each pH variation, contact time and concentration of Pb2+ metal ions were 2.4154 mg/g, 14,89 mg/g and 15,1732 mg/g.